PENGARUH METODE MIND MAPPING TERHADAP PEMBELAJARAN MENULIS TEKS EKSPOSISI PADA SISWA SMP - Damayanti, Dini; Ismayani, Mekar (IKIP Siliwangi, 2019)
This research is motivated by the difficulties faced by students when writing exposition texts, one of which is that there are still many students who complain in developing ideas to make a writing and lack of students' understanding of the exposition text structure. To overcome this problem, we need a learning method that has never been applied to students, namely the mind mapping method. Mind mapping method can increase students to write exposition text, because it can store material easily into the brain and can easily be expressed again. In this study, researchers used the experimental method by collecting data in the form of initial tests (pre-test) and final tests (post-test) with a sample of 30 MTs students. Based on the data obtained, the comparison of the results of learning exposition text writing with a mind mapping method can affect the learning process. Evidence states that the comparison results obtained by students are quite significant, before using mind mapping methods obtain an average of 73.2 and after using the mind mapping method obtain an average of 81.36. So, writing learning using the mind mapping method can be used in the classroom in learning exposition text writing.